Moral hazard in Australian private health insurance: the case of dental care services and extras cover - Nguyen, Lan; Worthington, Andrew C (My University, 2021)
We assess ex post moral hazard in Australian private health insurance (PHI) relating to dental care services (so-called extras cover) using the longitudinal Household, Income and Labour Dynamics in Australia (HILDA) Survey. Cross-sectional probit regressions specify dental care use as a function of dental care demand and endogenous PHI policy holding, including self-assessed health condition, health risk factors and socio-economic controls including age, income, education, family structure and welfare status. We find that ex post moral hazard results in the additional use of dental care services by PHI holders. Further, dynamic analysis indicates that PHI, no matter how sporadic, is always associated with significantly more likely use of dental care services, increasing when continuously held, suggesting strong persistence in moral hazard.
The Geneva Papers on Risk and Insurance - Issues and Practice
Keywords: Health and wellbeing